Caracterização genética e antigênica de isolados brasileiros do vírus da diarréia viral bovina - Bianchi, Eloisa (2011)
Bovine viral diarrhea virus (BVDV) isolates display a high genetic and antigenic variability that can compromise diagnosis and vaccine formulation. This study aimed to characterize at genetic and antigenic levels Brazilian BVDV isolates for potential use in diagnosis and vaccine production, and to characterize field BVDV isolates from Rio Grande do Sul (RS) (2000-2010). Chapter 1 describes the genetic and antigenic characterization of seven cytopathic Brazilian BVDV isolates, to select the most appropriate for use in diagnostic and vaccines. Sequencing and phylogeny identified four isolates of BVDV-1 (57.1%) and three isolates of BVDV-2 genotype (42.8%). The antigenic characterization of these isolates by virus neutralization assay (VN) with homologous and heterologous antisera revealed differences among the viruses of the same genotype, but especially among viruses of different genotypes. Despite the antigenic differences, the neutralizing activity of antisera IBSP-4 and VS26/2 was acceptable against isolates of the same genotype and also against viruses of different genotype. These results qualify these isolates for potential use in vaccine formulations. In parallel, 446 field serum samples were tested against the seven isolates and reference strains. Neutralizing antibodies anti-BVDV were found in 221 (50.3%) samples, and 198 (89.6%) had neutralizing activity against the both genotypes (Singer, BVDV-1 and VS- 253, BVDV-2), 18 (8.1%) serum samples and five (2.2%) neutralized only the standard BVDV-1 and BVDV-2. These results confirm that the antigenic differences between isolates may result in false-negative results, yet might not justify the performance of VN using both BVDV genotypes. Chapter 2 presents a genotypic and antigenic profile of 20 BVDV isolates obtained in RS state, between 2000 and 2010. The isolates were isolated from a variety of clinico-pathological syndromes. Most samples (19 or 95%) belong to biotype non-cytopathic (NCP) and one isolate (5%) had a mixture of viruses NCP and cytopathic (CP). Sequencing and phylogenetic analyses identified nine isolates of BVDV-2 (45%), eight BVDV-1 (40%) and three atypical BVDV isolates. Analysis of reactivity with a panel of 20 monoclonal antibodies (mAbs) revealed a marked variability in the major envelope glycoprotein gp53/E2 among viruses of the same genotype, but especially between different virus genotypes. Virus neutralization assays (VN) with antisera of BVDV-1 and BVDV-2 reference strains against the isolates revealed variable levels of cross-reactivity between viruses of the same genotype, and lack or very low reactivity between viruses of different genotypes. These results indicate the presence of both genotypes of BVDV in the cattle population of RS and confirm the remarkable antigenic diversity of these isolates.